Programming of Job Shop Production Systems with Fuzzy Logic - Leguizamón Castellanos, Luis Eduardo (TECCIENCIA, 2018)
This article proposes a decision-making algorithm based on the "fuzzy logic" as an optimization technique, which allows to find a good solution to the problem of determining the priority (sequencing) of service or manufacture of jobs in the programming of intermittent production systems, Job Shop. The combinatorial nature and complexity of the problem motivates the exploration of other alternatives solutions to the traditionally used. Initially, the fuzzy logic controller structure (number of input variables, rules and output) is determined in accordance with the objective functions to be optimized. Triangular membership functions are selected for the batch size, the delivery date, the processing time, the number of tools required in each operation, and the priority of the processing the jobs. The fuzzy rules base is defined, and the controller model is formulated (fuzzification, evaluation and defuzzification). The algorithm is developed in Matlab’s ®Simulink ®Fuzzy logic toolbox, achieving better results than those obtained with other methods.